Rwanda’s Anti-Corruption Experience : Actions, Accomplishments, and Lessons - World Bank (World Bank, Washington, DC, 2020)
This study analyzes how Rwanda fought administrative corruption in the public sector over the last two decades. The focus on administrative corruption in the public sector is dictated by the difficulty of assessing, observing, and measuring corruption relating to state capture and by emphasis that Rwandan officials have placed on reducing corruption in the everyday workings of the public sector. It may touch on some dimensions of governance such as voice and accountability or the rule of law, it only analyses them through their relationship to corruption. The study is based primarily on face-to-face interviews conducted in December 2019 with key individuals in and close observers to the fight against corruption. This study increases awareness of Rwanda’s anticorruption experience, given its importance in Rwanda’s own development and its relevance to international anticorruption efforts. The study is organized as follows: the first section describes the evolution of corruption in Rwanda to provide context for anticorruption efforts. The second section discusses those efforts, with a focus on transforming norms and standards, on prevention, and on sanctions. The third section presents the main factors of success. The fourth section identifies the lessons that can be drawn from Rwanda. The fifth section reflects on the remaining challenges in the country’s anticorruption journey.